Mesastasia mirabilis gen. et sp. n. (Protozoa, Euglenoididae)—новый паразит кишечника циклопов - Палиенко, Л.П.; Монченко, В.И. (Вестник зоологии, 1979)
Mesastasia mirabilis gen. et sp. n. from Mesocyclops leuckarti, Thermocyclops cras-sus and Th. dybowskii (vicinity of Kiev is described. It differs from the previously known species of Astasia and Parastasia by the larger flagellated individuals (180-230 um long with the flagellum 40 um long), by the abundance of small paramile granules and by other features. 32 daughter cells of the generative part of the life cycle continue dividing (including longitudinal division) forming a large number of very minute flagellated forms. The new engens occupies a phylogenetically intermediate position between the early known genera.